Comparative studies of radiation-protection fillers for composite materials based on fosfogipsum binder - Булат, Анатолий Федорович; Иванов, Валерий Анатолиевич; Звягильский, Ефим Леонидович; Голов, Константин Сергеевич; Большаков, Владимир Иванович (Eastern-European Journal of Enterprise Technologies, 2015)
The results of comparative experimental studies of the effect of various radiation-protection (RP) fillers for composite materials based on phosphogypsum binder on their RP properties were considered. The regularities of the influence of the parameters of X-ray protection structures, such as thickness, RP filler concentration, composite material density and matrix, etc. on the level of radiation protection of personnel taking into account the properties of phosphogypsum-based composite materials were established and, thus, creation technology parameters and efficiency of such structures were substantiated. The high efficiency of the rare earth elements (REE) as RP fillers for the phosphogypsum binder at a concentration of 30% by weight is associated with high RP properties at significantly lower cost compared to other investigated RP fillers. Comparative experimental studies have convincingly shown that REE are technologically advanced and the most efficient RP filler for gypsum binder, which offers the prospect of creating X-ray protection means (including collective) of a new technological level.